Low-carbon economic dispatch of integrated energy system considering carbon trading mechanism and LAES-ORC-CHP system - Zhou, Wei; Sun, Yonghui; Zong, Xuanjun; Zhou, Hongwei; Zou, Sheng (Frontiers in Energy Research, 2023)
Under the theme of low carbon, in order to improve the economy of integrated energy system (IES), optimize the operational flexibility of equipment, and further reduce the carbon emission level of IES, a low-carbon economy operation strategy of IES is proposed. Firstly, integrated energy system is considered to participate in the carbon trading market, and carbon trading mechanism is introduced to control the carbon emissions of the system. Secondly, based on the working characteristics of liquid air energy storage (LAES), organic Rankine cycle (ORC) and combined heat and power (CHP), LAES-ORC-CHP system is established in IES to achieve flexible supply of heat and power. Then, aiming at minimizing the sum of system operation costs and carbon transaction costs, the low-carbon economy optimal dispatch model of IES is proposed. Finally, the effectiveness of the proposed model is verified by setting multiple operation scenarios. Simulation results show that the proposed model can fully consider and balance the economy and low carbon of the system, and can provide a reference for the low-carbon economic dispatch operation of IES.